Development of monoclonal antibodies and serological assays including indirect ELISA and fluorescent microsphere immunoassays for diagnosis of porcine deltacoronavirus. Issue 1 (December 2016) - Okda, Faten; Lawson, Steven; Liu, Xiaodong; Singrey, Aaron; Clement, Travis; Hain, Kyle; Nelson, Julie; Christopher-Hennings, Jane; Nelson, Eric
Abstract Background A novel porcine deltacoronavirus (PDCoV), also known as porcine coronavirus HKU15, was reported in China in 2012 and identified in the U.S. in early 2014. Since then, PDCoV has been identified in a number of U.S. states and linked with clinical disease including acute diarrhea and vomiting in the absence of other identifiable pathogens. Since PDCoV was just recently linked with clinical disease, few specific antibody-based reagents were available to assist in diagnosis of PDCoV and limited serological capabilities were available to detect an antibody response to this virus. Therefore, the overall objective of this project was to develop and validate selected diagnostic reagents and assays for PDCoV antigen and antibody detection. Results The nucleoprotein of PDCoV was expressed as a recombinant protein and purified for use as an antigen to immunize mice for polyclonal, hyperimmune sera and monoclonal antibody (mAb) production. The resulting mAbs were evaluated for use in fluorescent antibody staining methods to detect PDCoV infected cells following virus isolation attempts and for immunohistochemistry staining of intestinal tissues of infected pigs. The same antigen was used to develop serological tests to detect the antibody response to PDCoV in pigs following infection. Serum samples from swine herds with recent documentation of PDCoV infection and samples from expected naïve herds were used for initial assay optimization. The tests were optimized in a checkerboard fashion to reduce signal to noise ratios using samples of known status. Statistical analysis was performed to establish assay cutoff values and assess diagnostic sensitivities and specificities. At least 629 known negative serum samples and 311 known positive samples were evaluated for each assay. The enzyme linked immunosorbent assay (ELISA) showed diagnostic sensitivity (DSe) of 96.1 % and diagnostic specificity (DSp) of 96.2 %. The fluorescent microsphere immunoassay (FMIA) showed a DSe of 95.8 % and DSp of 98.1 %. Both ELISA and FMIA detected seroconversion of challenged pigs between 8–14 days post-infection (DPI). An indirect fluorescent antibody (IFA) test was also developed using cell culture adapted PDCoV for comparative purposes. Conclusion These new, specific reagents and serological assays will allow for improved diagnosis of PDCoV. Since many aspects of PDCoV infection and transmission are still not fully understood, the reagents and assays developed in this project should provide valuable tools to help understand this disease and to aid in the control and surveillance of porcine deltacoronavirus outbreaks.